2014
DOI: 10.7763/ijiet.2014.v4.462
|View full text |Cite
|
Sign up to set email alerts
|

Can Higher Education Exams Be Shortened? A Proposed Methodology

Abstract: Abstract-Any lecturer would agree that marking exams is the bane of her existence. A time-consuming and tiring process, it often requires complex, subjective judgments. Higher education exams typically take 3.0 hours. Do they really need to last so long? Can we justifiably reduce the number of questions on them? Shortening an exam by one hour, if justified, should result in a one-third reduction in lecturer time and effort spent marking. Surprisingly little empirical research has addressed these problems. Clas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…Running paper‐and‐pencil exams for large classes (e.g., 200+ students) presents management challenges that include requesting space, printing exams, proctoring, timely grading, and handling conflict exams (Lee, Garg, Bygrave, Mahar, & Mishra, ; Muldoon, ; Zilles et al, ). These logistic burdens discourage faculty from using pedagogies that have been shown to improve student learning, such as frequent testing (Bangert‐Drowns, Kulik, & Kulik, ; Leeming, ) and mastery learning (Kulik, Kulik, & Bangert‐Drowns, ; Pennebaker, Gosling, & Ferrell, ), and have led to the overuse of multiple‐choice exams (Scouller, ; Stanger‐Hall, ).…”
Section: Introductionmentioning
confidence: 99%
“…Running paper‐and‐pencil exams for large classes (e.g., 200+ students) presents management challenges that include requesting space, printing exams, proctoring, timely grading, and handling conflict exams (Lee, Garg, Bygrave, Mahar, & Mishra, ; Muldoon, ; Zilles et al, ). These logistic burdens discourage faculty from using pedagogies that have been shown to improve student learning, such as frequent testing (Bangert‐Drowns, Kulik, & Kulik, ; Leeming, ) and mastery learning (Kulik, Kulik, & Bangert‐Drowns, ; Pennebaker, Gosling, & Ferrell, ), and have led to the overuse of multiple‐choice exams (Scouller, ; Stanger‐Hall, ).…”
Section: Introductionmentioning
confidence: 99%
“…Evaluation criteria for SFs mainly deal with proper representation of the measured construct, or a uniform allocation of items in subscales if the tool is multi-dimensional. These problems may be described by empirical criteria, the most important of which are: 1) SF reliability; 2) validity (mainly face and content validity relative to the FF); 3) the extent to which the SF reproduces the structure of the FF (this is the criterion is often used in abridgement reports); 4) similar pattern of relationships with other variables to the FF, particularly with respect to demographic variables, such as age or education, but also personal traits and characteristics (see also Lee et al, 2014).…”
Section: Questionnaires Abridgement 21mentioning
confidence: 99%
“…The last stage of SF creation should consist of assessing the classification accuracy of the SF by comparing the results with classification based on the FF. Lee et al (2014) suggested a threshold of r > .90 of correlation between raw scores on the SF and FF. Ultimately the SF cannot be significantly different from FF nor should it serve another goal than the one selected by a researcher.…”
Section: Questionnaires Abridgement 21mentioning
confidence: 99%
See 1 more Smart Citation